Budaya 3S (Senyum, Sapa, Salam) sebagai Implementasi Living Sunnah: Refleksi Konseptual Guru TPQ At-Taisir Banjarmasin - Muhaimin; Hairul Hudaya (Advances In Education Journal, 2026)
This study examines the implementation of the Prophet Muhammad’s sunnah as a form of living hadith in strengthening students’ social morality through the practice of the 3S culture (smile, greeting, and salutation) at TPQ At-Taisir. The research addresses the problem of declining social ethics among students and aims to analyze how the internalization of the sunnah influences their daily social interactions. This study employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings show that the habituation of smiling, gentle behavior, and polite interaction, rooted in the Prophet’s sunnah, contributes significantly to the formation of positive social character, including friendliness, respect, empathy, and harmonious relationships among students. Furthermore, the implementation of living sunnah creates a more conducive learning environment and strengthens students’ spiritual awareness. In conclusion, the application of the Prophet’s sunnah through the 3S culture plays an important role in shaping students’ social morality and fostering sustainable Islamic character education.